Emergency room thoracotomy for acute traumatic cardiac tamponade caused by a blunt cardiac injury: A case report - Ishida, Kenichiro (Int J Surg Case Rep, 2017)
INTRODUCTION: Traumatic blunt cardiac injuries have a high mortality rate, and prompt diagnosis and treatment can be lifesaving in cardiac tamponade. PRESENTATION OF CASE: A 62-year-old man was transferred to the emergency department after a motor vehicle accident. He was hemodynamically unstable. A focused assessment with sonography in trauma (FAST) showed pericardial fluid with right ventricular collapse consistent with cardiac tamponade in the subxiphoid view. He collapsed despite a subxiphoid pericardiotomy. Owing to the ongoing hemodynamic instability, we performed a left anterolateral thoracotomy. Direct incision of the pericardium showed blood and clots within the pericardial space, indicating hemopericardium. The heart stroke and hemodynamic status recovered on removing the clot. DISCUSSION: Although the physical findings of cardiac tamponade are not always apparent in life-threatening acute cardiac tamponade after blunt trauma, FAST is a reliable tool for diagnosing and following cardiac tamponade. A median sternotomy is a standard approach for evaluating cardiac injury in hemodynamically stable patients with or without cardiopulmonary bypass. However, a left anterior thoracotomy was the fastest, simplest life-saving procedure considering the need for open-chest cardiac massage given our patient’s life-threatening condition. CONCLUSION: A prompt diagnosis using FAST and treatment can be lifesaving in traumatic acute cardiac tamponade. A pericardiotomy via a thoracotomy is mandatory for lifesaving cardiac decompression in acute traumatic cardiac tamponade in cases of ineffective drainage due to clot formation within the pericardial space.